Akulturasi Budaya Jawa dan Islam Pada Pelaksanaan Tradisi Ruwahan di Langensari Baluwarti Pasar Kliwon Surakarta: Penelitian - Ahmad Zaini Anwar; Imam Muhsin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The acculturation between Javanese culture and Islam has resulted in various traditions, such as the ruwahan tradition. Although this tradition is carried out in almost every region in Indonesia, in fact there are differences in the implementation procession and meaning of the tradition. This research describes the acculturation of Javanese and Islamic culture in the ruwahan tradition in Langesari Hamlet, Baluwarti Village, Surakarta City. The method used in this research is a qualitative historical method, namely, heuristics, verification, interpretation, and historiography. The data collection method in this research is literature study and field study. The results of this study indicate that the ruwahan tradition in Langensari Hamlet, especially in a series of event processes, is the result of acculturation between Javanese culture and Islamic culture. This is evidenced by the existence of dhikr and tahlil, as well as solawat and Javanese songs included in the series of ruwahan events in Langensari Hamlet. Regarding the benefits of this research is as information material about the ruwahan tradition in Langensari Baluwarti Pasar Kliwon Surakarta. Then it is expected that the community should feel proud and always preserve it as a local cultural entity of a region. The values contained in the nyadran tradition include respect for parents (ancestors), sharing (alms), togetherness and harmony, preserving local culture.